Management consultants, the state, and the politics of administrative reform in Britain and Canada - Saint-Martin, Denis (1998)
Recent contributions to the literature on bureaucratic reform suggest that profit-seeking consultants from the private sector are one of the main driving forces behind the global spread of New Public Management (NPM) ideas. But contrary to what is expected, the growing role of consultants in the construction of the "post-bureaucratic state" in Britain and Canada did not lead to policy uniformity or convergence in the acceptance of NPM ideas. To explain these differences, the article focuses on the ways in which the differential access of consultants to decision-making centers inside the state influenced the application of the business management ideas that they bring to the policy process. - Reproduced
Keywords: Administrative reform - Canada; Administrative reform - Great Britain; Administrative reform